Students' learning experiences with synchronised emergency remote online education (Innovative Journal of Curriculum and Educational Technology, 2022)
The global intervention by universities to minimise the devastating effect of the COVID-19 pandemic on education compelled many institutions to resort to emergency online curriculum facilitation, especially using virtual platforms. As a result, institutions adopted asynchronous, or synchronous, or both to facilitate knowledge with students. This study explored the reality of students' experiences with contemporaneous (synchronous) online teaching and learning model adopted by a university in South Africa. This study employed an interpretive qualitative methodological design. Data was gathered through an open-ended questionnaire administered to twenty students purposively sampled from a population of sixty-eight rurally resident final year students and focus group interviews with six of the twenty students. Data was analysed using constructs generated from connectivism theoretical framing which served as the compass used to navigate the study. The study revealed digital interaction space to be new to many students, especially those from the deep rural areas of South Africa. Furthermore, institutional readiness was limited, hence lack of support (awareness, resources, etc.) for students at the initial implementation stage of the programme. However, students and university academics were committed, coupled with self-discipline, and through social and academic engagements, benefited from the system. Flexibility, continuous academic interaction with peers, instantaneous authentic feedback and improved proficiency in using online tools were their constructive experiences. Nonetheless, they highlighted concerns of perceptions, bad network and poor connectivity, less cognitive engagement and unsuitable learning environments. The study recommends the introduction of asynchronous alongside the synchronous model of curriculum engagement to enhance the flexibility of learning opportunities.